Understanding retirement in the UK - Jonathan Cribb (Institute for Fiscal Studies (IFS), 2023)
This report is designed to provide new evidence on retirement patterns in the UK, as part of the Pensions Review, a larger project run by the IFS in partnership with the abrdn Financial Fairness Trust, which is examining the future of financial security in retirement. Understanding patterns of retirement at older ages is key to understanding the challenges facing pensions systems, as pensions are designed to enable households to finance spending in old age when people are no longer in paid work. This report seeks to understand how patterns of employment and retirement have changed, both before and after state pension age, and how people finance their retirement. Where possible, we draw on the latest data in order to show the labour market and retirement behaviour of people aged 50-74 since the COVID-19 pandemic.
Keywords: 330; Employment and income; Savings; pensions and wealth; The pensions review; Retirement; Wealth; Ageing; Disability; Gender; Health; Wealth; Labour supply and workforce